First‐episode psychosis: Ongoing mental health service utilization during the stable period for adolescents. Issue 4 (11th October 2016) - Gearing, Robin E.; Brewer, Kathryne B.; Mian, Irfan; Moore, Kiara; Fisher, Prudence; Hamilton, Jane; Mandiberg, James
Abstract: Aim: The timely identification and treatment of psychosis are increasingly the focus of early interventions, with research targeting the initial high‐risk period in the months following first‐episode hospitalization. Ongoing treatment after stabilization is also essential in the years following a first‐episode psychosis (FEP), but has received less research attention. In this study, variables that could impact continued psychiatric service utilization by adolescents following their FEP and temporal patterns in service utilization are examined. Methods: Families of 52 adolescents (aged 14.4 ± 2.5 years) discharged following a hospitalization for FEP were contacted two or more years following the adolescents' discharge. A chart review (Time 1) of hospital records provided clinical data on each adolescent's psychiatric diagnosis, symptoms, illness course, medications and family history. Follow‐up (Time 2) data were collected from parents/caregivers using a questionnaire enquiring about post‐discharge treatment history and service utilization. Results: Bivariate analyses were conducted to identify Time 1 variables associated with psychiatric service utilization at Time 2. Significant variables were included in a logistic regression model and three variables were independently associated with continued service utilization: having a primary diagnosis of schizophrenia (odds ratio (OR) = 24.0; P = 0.02), not having a first‐degree relative with depression (OR = 0.12; P = 0.05) and fewer months since the last inpatient discharge (OR = 0.92; P = 0.02). Conclusions: Findings suggest: (1) the importance of early diagnosis, (2) that a relative with depression may negatively influence the adolescent's ongoing service utilization, and (3) that 18 months post‐discharge may be a critical time to review treatment strategies and collaborate with youth and families to ensure appropriateness of services.